COVID-19 Preventative Measures: Facemasks and Cloth Face Coverings - Michelle D. Danyluk; Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman (EDIS)
This one-page color fact sheet depicts the essential components of a facemask and anwers the following questions about facemasks for non-medical uses: